Assessing competitiveness of live sheep export in selected states in Sudan using policy analysis matrix - Ahmed Awad, Elsedig Elbadawi (2012)
The agriculture sector in Sudan, like in most developing countries, plays an important role in the country’s economic development, functioning as food supplier, employment and export earning and a source of raw materials for the other industries. It contributed 49.8 percent to the Gross Domestic Product (GDP) in 1999 and had declined to 30.1 percent in 2009. The livestock sector represents an important and integral component of the agriculture exports. Its share in the country’s GDP was 20.9 percent in 2002 and it dropped to 16 percent in 2009. The livestock share in the total agriculture exports dropped around 59 percent from US$ 83 million in 2002 to US$ 49 million 2008. The major objective of this study is to evaluate the competitiveness of sheep export in three selected states in Sudan, which are Khartoum, Gadarif and North Kordofan. Other objectives are to measure the comparative advantage and to provide policy recommendations to improve the competitiveness of sheep export in Sudan. The study employed secondary and primary data, which was collected in 2010. The Policy Analysis Matrix (PAM) was applied to determine the competitiveness and policy effects. The Nominal Protection Coefficient (NPC) and Effective Protection Coefficient (EPC) were used to analyse the policy effects. While the Domestic Research Cost (DRC) was used to determine the comparative advantage. The findings of this study illustrate the analysis of private profitability which shows that sheep of all sizes generate profit. The government interventions on sheep’s production in terms of taxes have negative impact on the competitiveness of sheep export in the selected states. Financially, the highest profit recorded in North Kordofan which is SDG 80.23 per head. The results of DRC indicator suggest that Sudan enjoys comparative advantage in production of sheep in selected states. North Kordofan has proven to be more effective in saving the foreign exchange, followed by Khartoum and Gadarif. The study recommends that the Government has to revise the tax structure, improve infrastructures and logistics, increase supportive measures (R&D to improve productivity), provides incentives and seeks markets to improve the competitiveness of sheep exports.